The Effect of Knowledge Sharing, Achievement Motivation, and Organizational Commitment on Employee Performance At Pt. Angkasa Pura II Pekanbaru - Marwansyah, Marwansyah; Hermansyah, Hermansyah (Economic: Journal Economic and Business, 2025)
This study aims to evaluate how organizational commitment plays a role in improving employee performance at PT. Angkasa Pura II Pekanbaru, by highlighting the influence of knowledge sharing practices and achievement motivation. The approach used is quantitative with an associative method. The research sample was selected using a stratified random sampling technique, involving 120 permanent employees as respondents. Data were collected through a questionnaire based on a semantic differential scale, and analyzed using SPSS 25 software and SmartPLS version 3.29. The results of the analysis show that both knowledge sharing and achievement motivation individually have a significant influence on organizational commitment. In addition, both factors also have a significant direct impact on employee performance. Other findings reveal that organizational commitment plays a significant mediating role in the relationship between knowledge sharing and achievement motivation on performance. This confirms that strengthening a culture of knowledge sharing and increasing motivation can strengthen employee commitment to the organization, which in turn has a positive impact on performance. This study is expected to be a practical reference in the preparation of human resource management strategies that focus on improving performance through strengthening organizational commitment in the workplace.